(3GYJQGVGJ GdCbUQGFi Ydi GdQGRi Ydi GdehGVY GdeTcdI ef GdcTGas - (3eMeO Hf eMeO Hf eMeO , LeGd GdOjf , GdCbSQGFj, J HO (B776 (3g`s ((3LeGd GdOjf Hf bQGFi s)
(3ChdgG (B:s
(3gh GdfHi hHYOg hGMO PcQ GdbWH hGdeUbGf HjfgeG s
(3BNQgG (B:s
(3hEfeG jbY ai hbJ GdNWGH (B,(3hcGf GdaQGZ ef cJHJg s
(3JHUQI GdYfhGf (B:s
(3JYbjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B6(3GdChd (B- s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs